Improved resolution and speed in nonlinear microscopy - Masihzadeh, Omid, author; Bartels, Randy A., advisor; Roberts, Jacob Lyman, committee member; Menoni, Carmen S., committee member; Marconi, Mario C., committee member (Colorado State University. Libraries, 2010)
Optical microscopy is an important tool for biomedical research. New techniques for microscopy enable new capabilities for studying biological systems. Moreover, in optical microscopy, the polarization state of the focal field strongly influences the images formed due to the impact of focal spot size, adjusting the relative strength and phase of both transverse and longitudinal field components, and manipulating inter- action with the sample under study. In particular, coherent nonlinear microscopies, such as third harmonic generation (THG), and second harmonic generation (SHG), offer rich possibilities for new control over the imaging process. In the first part of this dissertation, I demonstrate that control over the spatial polarization state of the focal field can be used to improve the spatial resolution in a laser-scanning THG microscopy. First, we show a detailed design of our nonlinear scanning microscope, then we introduce a non-iterative algorithm for measurement of spatially inhomogeneous polarization distributions in third-harmonic generation microscopy. We also, show control of spatial polarization state of the focal field through imaging of a spatial light modulator to the focus of a microscope objective. Then, we introduced a novel technique for enhancing resolution in THG microscopy, through spatial polarization shaping at the focal field. In the second part of this dissertation, we show an alternative method to laser- scanning nonlinear microscopy in biological tissue, namely, nonlinear holographic microscopy. First, we introduce the foundation of nonlinear holographic microscopy by reviewing linear off-axis holography. We start by introducing digital recording in off- axis holography, its limitations, and show how through holography we can obtain 3-D images from 2-D data. We then explore numerical reconstruction of the object field from the recorded holograms. Finally, we expand this technique to SHG nonlinear holographic microscopy to construct 3-dimensional images of biological tissues.
Department Head: Anthony A. Maciejewski.